PENGOLAHAN SAMPAH ORGANIK DI LINGKUNGAN SEKOLAH MENJADI KOMPOS - Ayu Lestari; Elni J. Usoh; Jeffry S.J Lengkong (LPPM Universitas Cipta Mandiri, 2024)
This project was carried out with the aim of providing knowledge and skills for students in processing organic waste, especially organic waste located around the school environment. There are 37 students taking part in a project to manage organic waste. This project method begins by providing outreach or counseling regarding the stages that will be followed to manage organic waste into compost, providing materials and tools as well as a compost bin, training in making compost and knowledge about waste to students at SMA Negeri 7 Manado. The results obtained from the projects that have been carried out are that students are more aware of the waste problem around them, and it also provides them with new skills so they can process waste into compost that can be used personally or can be a product that can be sold.